Fourth National Information Day and Workshop: Open Access to Scientific Information and Data - Stanchev, Peter; Simeonov, Georgi (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2013)
The paper presents in brief the “2 nd Generation Open Access Infrastructure for Research in Europe” project (http://www.openaire.eu/) and what is done in Bulgaria during the last year in the area of open access to scientific information and data.
Keywords: Open access